EXPRESSING DEONTIC MODALITY: OBLIGATION IN RUSSIAN AND UKRAINIAN INTERNATIONAL LAW - GOLETIANI, Liana (Comparative Legilinguistics, 2016)
The aim of this paper is to compare the Russian and Ukrainian clauses conveying deontic modality of obligation in international law. The investigation was carried out on parallel texts of Agreement, Treaty and Memorandum of Understanding drawn up by the Ukraine and the Russian Federation in the post-Soviet era. This systematic comparison deals with both modal auxiliaries and several periphrastic constructions. The study findings show that the two languages have very different constructions for conveying this deontic value, with Ukrainian legal language using a more varied range of lexico-semantic and morphosyntactic units. Divergence occurs in the use of the modal constructions with the verbs musyty and maty and the synthetic future form, which is not available in Russian.